Single-line administration - An administrative experiment in Jammu and Kashmir - Aivalli, Veeranna (1998)
Presenting case of Ladakh, where single-line administration operates, the author discusses its background, features and advantages that have flowed from it in terms of better coordination among development departments at district level, qualitative change in working of government departments, democratic decentralisation and better administrative accountability. He also briefly discusses the drawbacks of the system before commending the success of the system. - Reproduced
Keywords: Public administration - India - Jammu and Kashmir; Public administration